先化简, 再求代数式 $\left(\frac{1}{x-1}-\frac{x-3}{x^2-2 x+1}\right) \div \frac{2}{x-1}$ 的值, 其中 $x=2 \cos 45^{\circ}+1$.
【答案】 【详解】解: 原式 $=\left[\frac{x-1}{(x-1)^2}-\frac{x-3}{(x-1)^2}\right] \cdot \frac{x-1}{2}$
$$
\begin{aligned}
& =\frac{(x-1)-(x-3)}{(x-1)^2} \cdot \frac{x-1}{2} \\
& =\frac{2}{(x-1)^2} \cdot \frac{x-1}{2} \\
& =\frac{1}{x-1} \\
& \because x=2 \times \frac{\sqrt{2}}{2}+1=\sqrt{2}+1 \\
& \therefore \text { 原式 }=\frac{1}{\sqrt{2}+1-1}=\frac{1}{\sqrt{2}}=\frac{\sqrt{2}}{2} .
\end{aligned}
$$


系统推荐